A redefinition and review of the genus Myrmolimosina Marshall (Diptera: Sphaeroceridae), with morphological and molecular assessments of new species from Mexico and Guatemala. Issue 6 (17th March 2015) - Marshall, Stephen A.; Skevington, Jeffrey H.; Kelso, Scott; Zhou, Claudia
Abstract: The previously monotypic genus Myrmolimosina Marshall (Diptera: Sphaeroceridae) is expanded to include thenew species M. batus Marshall from Guatemala and Mexico and M . llama Marshall from Mexico, and redefined to include specimens with and without the strongly petiolate abdomen reflected in the generic name. Myrmolimosina batus is known only from females and M. llama is known only from males. The possibility that these two putative species represent the same sexually dimorphic species is considered and rejected based on molecular data.